Motivation And Compensation As Predictors Of Employees’ Retention: An Empirical Study Of A Public Sector Organization - SOOMRO, DR. MANSOOR AHMED; HUSSAIN, DR. NAZAR; MAITLO, DR. ABDULLAH; LASHARI, IRFAN AHMED (The journal of contemporary issues in business and government, 2021)
Pakistan is a developing country, where employee retention is a fast-growing subject and it is considered a unique form of an idea. The unusual economic changes of today’s era are directly connected with the employees’ progress and growth in an organization, it is analyzed that the retention of employees’ is connected with his growth and promotions. If the employee is provided with timely and due promotions then these are retained otherwise they seek options to turnover. The study examined the impact of motivation and compensation on employee retention in Sui southern gas company Dadu. The data was collected from the very professional public sector Sui Southern Gas Company Limited Dadu in the form of 80 questionnaires from different employees of various SSGCL sections. The data are analyzed through statistical tests and multiple techniques. The results show that constant improvement in motivation level and practical exercise of compensation might bring improvement in employee‟ retention. Motivation and compensation are directly associated with employee retention. The recommendations of this study are very useful for the company’s (SSGCL) management, various strategies and implications are recommended for policymaking.